Folding of fluorinated oligoarylenes into non-alternant PAHs with various topological shapes - Akhmetov, Vladimir; Foertsch, Andreas; Feofanov, Mikhail; Troyanov, Sergey; Amsharov, Konstantin (Organic Chemistry Frontiers, 2020)
An unprecedented [6]helicene's cavity closure indicating the possibility of introducing seven-membered rings via alumina-mediated C-F activation is shown. This finding, in combination with a directed quadruple annulation of fluorinated oligoarylenes, opens a short pathway to elusive non-alternant PAHs. Starting with one fluorinated block, we have synthesized through a two-step procedure three new representatives with helical-, bowl- and saddle-shapes. Additionally, the structure-property relationship in these new PAHs is explored via theoretical, optical, and X-ray crystallographic studies.
CRIS-Team WoS Importer:2020-06-16